2012
DOI: 10.1530/eje-12-0147
|View full text |Cite
|
Sign up to set email alerts
|

Progression of acromegalic arthropathy despite long-term biochemical control: a prospective, radiological study

Abstract: Objective: Arthropathy is an invalidating complication of acromegaly, of which the prognosis and determinants are currently unknown in treated acromegaly. Therefore, the objective of the present study was to investigate the radiographic progression of arthropathy over a mean follow-up period of 2.6 years and determinants of outcome in patients with long-term, well-controlled acromegaly. Design: Prospective follow-up study. Methods: In a prospective cohort study we studied 58 patients (mean age 62, women 41%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 50 publications
4
48
1
4
Order By: Relevance
“…Recently, it has been reported that despite long-term biochemically controlled disease, more than 70% of patients have progressive osteophytosis and/or JSN [85]. The highest radiographic progression rate was seen in older patients and in patients with higher GH/IGF-1 activity.…”
Section: Acromegalic Joint Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that despite long-term biochemically controlled disease, more than 70% of patients have progressive osteophytosis and/or JSN [85]. The highest radiographic progression rate was seen in older patients and in patients with higher GH/IGF-1 activity.…”
Section: Acromegalic Joint Diseasementioning
confidence: 99%
“…The highest radiographic progression rate was seen in older patients and in patients with higher GH/IGF-1 activity. Interestingly, the highest progression rate of joint disease was reported in medically treated patients compared to surgically cured patients [85]. Since GH secretion does not normalize during SMS treatment [86], subtle ongoing GH overproduction, despite normal IGF-1 levels, may explain the increased progression rate in these patients.…”
Section: Acromegalic Joint Diseasementioning
confidence: 99%
“…4 However, current therapies focusing on the GH/IGF-1 axis are only effective in approximately 28% of acromegalic patients, while the remaining 72% of patients have continuing excessive bone growth or abnormal bone metabolism even after GHPA shrinkage or GH/IGF-1 level normalization. [5][6][7][8] These facts strongly suggest that another pathogenic mechanism is essential in the majority of acromegaly cases. In this study, the relationship between GHPA and osteoblasts was explored by studying GHPA exosomes, with the goal of providing a new perspective for evaluating acromegaly mechanisms.…”
Section: Introductionmentioning
confidence: 94%
“…Musculoskeletal-related disorders account for the main functional disability in patients with acromegaly [3]. Following successful treatment of acromegaly, some features of the disease may show partial reversibility [4], but results are conflicting [5]. Concerning the hands of patients in long-term remission of acromegaly, the late effects of the disease have not been fully characterized [6].…”
Section: Introductionmentioning
confidence: 99%